New Readings in Arabic Historiography from Late Medieval Egypt and Syria Proceedings of the themed day of the Fifth Conference of the School of Mamluk Studies - van Steenbergen, Jo; Termonia, Maya (Islamic History and Civilization, 2021)
The present volume contributes to research on historic Arabic texts from late medieval Egypt and Syria. Departing from dominant understandings of these texts through the prisms of authenticity and "literarization," it engages with questions of textual constructedness and authorial agency. It consists of 13 contributions by a new generation of scholars in three parts. Each part represents a different aspect of their new readings of particular texts. Part one looks at concrete instances of textual interdependencies, part two at the creativity of authorial agencies, and part three at the relationship between texts and social practice. New Readings thus participates in the revaluation of late medieval Arabic historiography as a critical field of inquiry. Readership: All interested in medieval history and Islamic history, especially Mamluk studies, and anyone concerned with historiography and Arabic literature.